2013
DOI: 10.1002/ar.22657
|View full text |Cite
|
Sign up to set email alerts
|

Double Outlet Right Ventricle Versus Aortic Dextroposition: Morphologically Distinct Defects

Abstract: This study concerns the morphological differentiation between double outlet right ventricle (DORV) and aortic dextroposition (AD) defects, namely tetralogy of Fallot and Eisenmenger anomaly. Indeed, despite the similar condition in terms of sequential ventriculo-arterial connections, DORV and AD are two distinct morphological entities. It is proposed that the borderline between these two groups of malformations is represented by the specific insertion of the infundibular septum into the left anterior cranial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…DORV was noted in 15.5% of the patients with SIT in our cohort, which is substantially higher than 1.2–2.7% in CHD patients without laterality disorders (Lowry et al, ; Miller et al, ; Pradat et al, ; van der Linde et al, ) and previous reports that 7.9% of SIT cases have DORV (Lin et al, ). Apart from ethnic difference (Zhao et al, ), the obviously higher prevalence rate of DORV in SIT than in situs solitus might be attributable to DORV having a common developmental path with laterality defects (Restivo, Unolt, Putotto, & Marino, ). Several genes that were implicated in the establishment of LR asymmetry, such as CFC1 (Obler, Juraszek, Smoot, & Natowicz, ) and ZIC (D'Alessandro, Latney, Paluru, & Goldmuntz, ), were found to be associated with DORV.…”
Section: Discussionmentioning
confidence: 99%
“…DORV was noted in 15.5% of the patients with SIT in our cohort, which is substantially higher than 1.2–2.7% in CHD patients without laterality disorders (Lowry et al, ; Miller et al, ; Pradat et al, ; van der Linde et al, ) and previous reports that 7.9% of SIT cases have DORV (Lin et al, ). Apart from ethnic difference (Zhao et al, ), the obviously higher prevalence rate of DORV in SIT than in situs solitus might be attributable to DORV having a common developmental path with laterality defects (Restivo, Unolt, Putotto, & Marino, ). Several genes that were implicated in the establishment of LR asymmetry, such as CFC1 (Obler, Juraszek, Smoot, & Natowicz, ) and ZIC (D'Alessandro, Latney, Paluru, & Goldmuntz, ), were found to be associated with DORV.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the paper by D'Alessandro et al which showed that mutations of ZIC3 in patients with d‐transposition of the great arteries (TGA), double outlet right ventricle (DORV), and heterotaxy confirms the previously reported suggestion that a subset of DORV and TGA may fall within the spectrum of laterality defects [Digilio et al, ; Goldmuntz et al, ; Marino et al, ; De Luca et al, ; Restivo et al, ]. However, the definition of DORV based simply on the assignation of both great arteries to the right ventricle is insufficient to permit proper genotype/phenotype correlation.…”
Section: To the Editormentioning
confidence: 54%
“…However, the definition of DORV based simply on the assignation of both great arteries to the right ventricle is insufficient to permit proper genotype/phenotype correlation. DORV is a type of ventriculo‐arterial connection and does not represent an uniform cardiac phenotype which several cardiologists have struggled to define [Restivo et al, ]. In particular DORV can coexist with “normally related and spiralized great arteries” with subaortic VSD in the context of aortic dextroposition, which has been associated with mutations of FOG2 [De Luca et al, ; Tan et al, ].…”
Section: To the Editormentioning
confidence: 99%
“…In my own experience, it is also not unusual, in the setting of right isomerism when there is double outlet from the right ventricle and a common atrioventricular junction, to find the interventricular communication in potentially subaortic position. This highlights another of the problems posed by the commentary offered by Restivo et al (2013). Although they state that their investigation failed to detect such hearts, they give no indication of the material on which their study is based.…”
mentioning
confidence: 88%
“…In many ways, the presence or absence of double outlet is the key decision to be made during the diagnostic work-up, since in such circumstances the surgeon will need to be told whether he or she will simply be closing a ventricular septal defect, or tunneling an interventricular communication to the subaortic outflow tract predominantly supported by the morphologically right ventricle. For that reason alone, double outlet right ventricle, despite the protestations of Restivo et al (2013), needs to be analyzed as one form of ventriculo-arterial connection, since the group of lesions sharing this feature has no phenotypic specificity.…”
mentioning
confidence: 99%